PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA YANG DIAJAR MENGGUNAKAN MODEL KOOPERATIF ANTARA TIPE STAD DENGAN TIPE JIGSAW PADA POKOK BAHASAN SEGI EMPAT DI KELAS VII SMP MUHAMMADIYAH 1 GENTENGTAHUN AJARAN 2011/2012 - Setyawan, Roni; Setiawan, Toto' Bara; Pambudi, Didik Sugeng (Kadikma, 2013)
Abstract.A comparison of the students learning outcomes by using STAD cooperative model with a jigsaw type ( experimental research at SMP Muhammadiyah 1 Genteng – Banyuwangi, Department of Mathematics Education and mathematics Science, the Faculty of Teacher Training and Education Jember University. The purpose of this research was to compare learning outcomes between students who were taught with cooperative learning model STAD type with jigsaw type. This study was conducted at SMP Muhammadiyah 1 Genteng. The total number of the students in grade VIIC and VIID was 66 students. The data was gathered by using achievement test and observation in form of questionnaire. The value of 5% significant coloum was 6,193 and the value of t table 5,671. It can be concluded that there was different mean score between cooperative learning STAD and Jigsaw. The result showed that in learning STAD class was 3,14 and the result of Jigsaw was 2,68. Thus it can be concluded that the learning by using cooperative learning jigsaw type better than classes taught by type STAD cooperative learning. Key Words : Cooperative Learning STAD Type, Cooperative Learning Jigsaw type, Achievement. Mathematics, Square